Pertemuan Islam dengan budaya lokal Hindu: Pengaruh masuknya Islam terhadap Agama Hindu di India - Hannani, Luthfia (Maliki Interdisciplinary Journal, 2024)
History is something that is considered boring by some people, but history is something that is important to be our reference in building the future. Especially as a Muslim, it is important for us to study Islamic history, because with it we can know the struggles of the figures who played a role in spreading Islamic teachings. There is a lot of Islamic history that we don’t know specifically, one of which is the Islamic civilization in India. This study aims to determine the history of the arrival of Islam in India and the influence of Islam on local Hindu culture in India and its advances. Islam is the second largest religion in India after Hinduism and progressed during the Mughal Dynasty. One such example is the conquest of all of western India by Jalalludin Muhammad Akbar. In spreading Islam there are many challenges, especially in Hindustan, where the majority of the population is Hindu. Islam was not immediately accepted by the population as a whole, the leaders did various ways to spread Islamic teachings. The arrival of Islam in India gave a touch of color to all existing aspects of life, like the countries that were conquered by Islam before. Starting from the political, economic, social, cultural aspects, to daily life so that Islam indirectly contributes to life in India, especially the acculturation of culture between Islamic culture and culture in India.